Village Fund Allocation, Area Size, and Population as Determinants of the Village Development Index : Alokasi Dana Desa, Luas Wilayah, dan Jumlah Penduduk sebagai Faktor Penentu Indeks Desa Membangun - Firmansyah, Yusma Amrulloh Tri; Yurianti, Viona Retha; Santoso, Slamet; Purnomo, Rochmat Aldy (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Village development remains a core priority in Indonesia’s national agenda, aiming to reduce underdeveloped areas and improve rural independence. Specific Background: Policies such as Village Fund Allocation (ADD) are central to these efforts, yet effectiveness varies widely across regions. Knowledge Gap: Prior studies largely use cross-sectional data and overlook spatial-temporal dynamics, failing to link ADD with sustainable financial management practices at the village level. Aims: This study investigates the influence of Village Fund Allocation, Village Area, and Population Size on the Village Building Index (IDM) in Ponorogo Regency from 2022–2024 using panel data regression. Results: Findings indicate that Village Fund Allocation has a significant negative effect, Population Size a significant positive effect, while Village Area has no significant effect on IDM. Collectively, these variables significantly influence IDM, though only explaining 27% of its variation. Novelty: The study offers a panel data approach combined with strategic financial management implications to capture local development dynamics more accurately than prior research. Implications: Results suggest the need for reorientation of fiscal strategies toward data-based planning and capacity building in local governance to optimize ADD’s role in achieving sustainable rural development.Highlight : Village Fund Allocation negatively and significantly affects the Village Building Index (IDM). Village Area does not have a significant effect on IDM. Number of Village Population positively and significantly contributes to IDM. Keywords : Village Fund Allocation, Village Area, Number of Village Population, Village Building Index, Panel Data